Preparation method of rapeseed oil with high polyphenol retention rate based on bionic enzymolysis

By simulating the vacuolar environment of plant cells with gradient porous ceramic filter elements, combined with buffer gel and enzyme-substrate pre-binding technology, the problems of polyphenol loss and phospholipid residue in rapeseed oil processing were solved, achieving efficient and stable enzyme catalysis and high polyphenol retention rate in rapeseed oil.

CN120843185APending Publication Date: 2025-10-28GUIZHOU CHANGSHUN BAMEI AGRI PROD DEV CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511089932.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

In traditional rapeseed oil processing, polyphenols are easily destroyed, leading to a decrease in nutritional value, and the problem of phospholipid residue is difficult to solve. Existing enzyme technologies and filtration materials suffer from low efficiency or high cost.

Method used

The gradient porous ceramic filter element is used to simulate the vacuolar environment of plant cells. Combined with buffer gel and enzyme-substrate pre-binding technology, the triple biomimetic design of gradient porous ceramic + buffer gel + enzyme-substrate pre-binding achieves efficient and stable enzyme catalysis, simulates the microenvironment of plant cell vacuoles, protects enzyme activity and selectively adsorbs phospholipids.

Benefits of technology

It achieves high polyphenol retention and deep phospholipid removal, maintaining the nutritional value and quality of rapeseed oil, reducing production costs, and avoiding the use of chemical reagents and food safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a preparation method of rapeseed oil with high polyphenol retention rate based on bionic enzymolysis. Comprising the following steps: raw material pretreatment: crushing rapeseeds and adjusting the water content; enzymatic hydrolysis activation: spraying a beta-glucosidase solution, and standing to obtain pretreated rapeseeds; low-temperature squeezing: feeding the pretreated rapeseeds into a screw press, and mounting a bionic ceramic filter element at an oil outlet; and directly filling the rapeseed oil flowing out of the bionic ceramic filter element to obtain the rapeseed oil. The bionic ceramic filter element is sintered by adopting a gradient sintering technology, forms a pore channel structure which is dense outside and sparse inside, and mainly comprises three layers: an outer layer: 5-10 [mu] m macropores and simulates a cell wall screen structure; the middle layer is a pore channel of 1-3 microns and is filled with a compound enzyme-buffer gel solution with the pH value of 5.5; the inner layer is provided with 50-100nm micropores which are used for adsorbing phospholipid. According to the method, the microenvironment of plant cell vesicles is simulated, and triple bionic design of gradient porous ceramic + buffer gel + enzyme-substrate pre-combination is adopted, so that efficient and stable enzyme catalysis is realized, and the rapeseed oil with high polyphenol retention rate is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oilseed processing, specifically relating to a method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis. Background Technology

[0002] Rapeseed oil, as an important edible vegetable oil, is not only rich in unsaturated fatty acids but also in polyphenolic active substances, such as glucosinolate hydrolysates and phenolic acids. These polyphenolic compounds have significant antioxidant and anti-inflammatory physiological activities, offering important benefits to human health. However, in traditional rapeseed oil processing, these active ingredients are often severely damaged, leading to a significant reduction in the nutritional value of the final product. Currently, the industrial production of rapeseed oil mainly faces the following key technical challenges: First, in the pretreatment and pressing stages, conventional high-temperature processing (temperatures typically exceeding 80°C) directly leads to the degradation of heat-sensitive polyphenols. Studies have shown that rapeseed oil that has undergone high-temperature pressing and subsequent refining often contains less than 40% of the potential polyphenol content in the raw material. This not only results in a loss of nutritional value but also affects the flavor characteristics of the oil. Second, in the oil refining process, traditional degumming and deacidification processes further cause the loss of polyphenols. In particular, hydration degumming and alkali refining processes cause a large amount of water-soluble polyphenols to be discharged with the degumming wastewater. More seriously, these processes often require the use of chemical reagents, potentially posing food safety risks. Third, phospholipid residue has long plagued rapeseed oil production. Conventional physical refining methods struggle to reduce phospholipid content below 50 ppm, and these residual phospholipids are prone to precipitation during storage, affecting not only product appearance but also accelerating oil oxidative rancidity. Regarding enzyme technology applications, while studies have attempted to use enzymes such as β-glucosidase to release bound polyphenols from rapeseed, significant technical bottlenecks exist. Free enzyme preparations are easily deactivated during processing and difficult to recycle, greatly increasing production costs. Existing immobilized enzyme technologies often face problems such as high carrier mass transfer resistance and low enzyme activity retention. Filtration technology also faces challenges. Traditional filter media either have pores that are too large to effectively trap colloidal impurities, or pores that are too small, leading to a sharp increase in filtration resistance, making them unsuitable for industrial production. Especially for low-temperature pressing processes, ensuring both filtration efficiency and maintaining the activity of functional components places even higher demands on filter materials. Therefore, developing a green manufacturing technology for rapeseed oil that can simultaneously achieve efficient retention of polyphenols and deep removal of phospholipids has become an important issue that urgently needs to be addressed in the current oil processing field. Summary of the Invention

[0003] Technical Problem to be Solved: To address the aforementioned problems, the purpose of this invention is to provide a method for preparing rapeseed oil with high polyphenol retention based on biomimetic enzymatic hydrolysis. By simulating the microenvironment of plant cell vacuoles, a triple biomimetic design of gradient porous ceramic + buffer gel + enzyme-substrate pre-binding is adopted to achieve efficient and stable enzyme catalysis, thereby obtaining rapeseed oil with high polyphenol retention.

[0004] Technical solution: A method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis, comprising the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 18-22%; S2. Enzymatic activation: Spray with β-glucosidase solution and let stand at 50-55℃ for 1-1.5h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press, and a biomimetic ceramic filter element is installed at the oil outlet; S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; The biomimetic ceramic filter element is sintered using gradient sintering technology, forming a porous structure with a dense outer layer and a sparse inner layer. It mainly consists of three layers: outer layer (oil inlet side): 5-10μm macropores, simulating the sieve structure of a cell wall; middle layer: 1-3μm pores, filled with a lemon complex enzyme-buffered gel solution at pH 5.5 (simulating the vacuolar environment); inner layer (oil outlet side): 50-100nm micropores, adsorbing phospholipids.

[0005] Furthermore, in step 2, the pH of the β-glucosidase solution is 5.5, and the spraying volume is 40 U / g rapeseed.

[0006] Furthermore, the parameters of the screw press in step 3 are: 53-57℃, screw speed 15-20rpm, and oil output speed 1.3-1.5L / min.

[0007] Furthermore, the preparation method of the biomimetic ceramic filter element is as follows, in parts by weight: S31. Raw material preparation: Outer layer: 35 parts talc, 38 parts kaolin, 15 parts α-alumina, 12-15 parts ordinary starch and 5 parts polyvinyl alcohol; Middle layer: 35 parts talc, 38 parts kaolin, 15 parts α-alumina, 8-10 parts graphite and 5 parts polyvinyl alcohol; Inner layer: 35 parts talc, 38 parts kaolin, 15 parts α-alumina, 10-12 parts starch nanocrystals, 4 parts polyvinyl alcohol and 2 parts polyethylene glycol 4000; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: 600℃ / 2h→1000℃ / 1h→1350℃ / 3h→800℃ / 1h, to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Dissolve the complex enzyme in 0.1 M citrate-phosphate buffer, add glucosinolate, pre-incubate at 45-48℃, pH 5.0, and 100-120 rpm for 40 min, add 1% trehalose, mix well to obtain the pre-incubation solution, then add a solution of 1% agarose and 0.1% CaCl2 to adjust the pH to 5.5 to obtain the complex enzyme-buffered gel solution; S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of (-0.08)-(-0.1) MPa for 40-60 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 300-500 rpm for 2 min to remove the residual composite enzyme-buffered gel solution on the outer layer. Cool and set at 4℃ for 10 min to obtain the final product.

[0008] Furthermore, in S31, the particle size of ordinary starch is 5-10 μm, the particle size of graphite is 1-3 μm, and the particle size of starch nanocrystals is 50-100 nm.

[0009] Furthermore, in step S33, the temperature is increased to 600°C at a heating rate of 5°C / min; increased to 1000°C at a heating rate of 3°C / min; increased to 1350°C at a heating rate of 3°C / min; decreased to 800°C at a cooling rate of 3°C / min; and then naturally cooled to room temperature after reaching 800°C.

[0010] Furthermore, the complex enzymes in S35 are cellulase, pectinase and β-glucosidase, and after dissolution, the cellulase concentration is 60 U / mL, the pectinase concentration is 40 U / mL, and the β-glucosidase concentration is (20-30) U / mL.

[0011] Furthermore, the molar ratio of β-glucosidase to glucosinolate in S35 is 1:2.

[0012] Furthermore, the volume ratio of the pre-incubation solution and the solution of 1% agarose and 0.1% CaCl2 in S35 is 1:(1-2).

[0013] Furthermore, every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flux.

[0014] The rapeseed oil with high polyphenol retention rate prepared by the above method.

[0015] Beneficial effects: 1. This invention simulates the microenvironment of plant cell vacuoles and adopts a triple biomimetic design of gradient porous ceramic + buffer gel + enzyme-substrate pre-binding to achieve efficient and stable enzyme catalysis and obtain rapeseed oil with high polyphenol retention.

[0016] 2. This invention utilizes a biomimetic ceramic filter element with a biomimetic structure (dynamic filtration and enzymatic hydrolysis). The outer layer (5-10μm macropores) mimics the sieve structure of plant cell walls, allowing large molecules (such as cell debris) in rapeseed oil to pass through while blocking fibrous impurities. The middle layer (1-3μm pores) is filled with a composite enzyme-buffered gel solution, mimicking the microenvironment of plant vacuoles, providing stable acid-base conditions, protecting enzyme activity, and immobilizing enzymes to continuously hydrolyze glucosinolates and release polyphenols. The inner layer (50-100nm micropores) has a semi-permeable structure similar to a vacuolar membrane, selectively adsorbing phospholipids and free fatty acids, thus improving the purity of rapeseed oil.

[0017] 3. This invention utilizes enzyme-substrate pre-binding immobilization technology, in which β-glucosidase is pre-binded with glucosinolates (a polyphenol precursor in rapeseed) to form an enzyme-substrate complex, which is then immobilized in a buffer gel. This immobilization method simulates the coexistence of enzyme and substrate in plants, enabling the enzyme to continuously and efficiently release polyphenols during the pressing process without being inactivated due to substrate concentration fluctuations.

[0018] 4. This invention stabilizes the enzyme structure and prevents denaturation by adding trehalose during pressing (55°C).

[0019] 5. This invention employs a stepwise mechanism of action of a complex enzyme: Cellulase: hydrolyzes β-1,4-glucan chains in the rapeseed cell wall, disrupting the fibrous skeleton; Pectinase: degrades pectin in the intercellular layer, releasing encapsulated oils and polyphenol precursors; β-glucosidase: Specific hydrolysis of glucosinolates releases sinapic acid (the core polyphenol).

[0020] 6. In the preparation of biomimetic ceramic filter elements, the composite enzyme-buffered gel can selectively remain in the middle layer (1-3 μm pores) without penetrating into the outer layer (5-10 μm) or inner layer (50-100 nm). This is mainly because the outer layer (5-10 μm macropores) cannot retain the gel. The agarose molecular chains in the buffered gel form a micron-scale network structure (typical pore size 1-5 μm). However, the gel as a whole is a continuous phase, and its flow characteristics are similar to viscoelastic fluid. When the gel is injected in liquid state, because the outer layer pore size is much larger than the gel network gap (5-10 μm vs 1-5 μm), the gel will flow through quickly due to low capillary force and cannot remain. When negative pressure is applied, the liquid gel in the outer macropores is drawn into the middle layer. The residual liquid gel can be removed by centrifugation in the later stage. The inner layer pore size (50-100nm) is much smaller than the gaps in the gel network (1-5μm), forming a physical barrier that prevents the large agarose molecules and enzyme complexes in the gel from entering. At the same time, the inner layer is almost unaffected by negative pressure due to the poor air permeability of the nanopores. The agarose forms a gel below 40℃, at which point the gel in the middle layer is mechanically locked in the 1-3μm pores due to volume expansion (sol-gel transition). Detailed Implementation

[0021] This invention proposes a method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following will provide a more detailed description of the invention with reference to specific examples. It should be understood that the specific examples described herein are only for explaining the invention and are not intended to limit the invention. Example 1

[0022] The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer (oil inlet side): 35g talc, 38g kaolin, 15g α-alumina, 12g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer (oil outlet side): 35g talc, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0023] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm. Example 2

[0024] The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0025] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0026] Example 3 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 15g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0027] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0028] Example 4 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 8g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0029] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0030] Example 5 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 10g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0031] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0032] Example 6 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 10g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0033] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0034] Example 7 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 12g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0035] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0036] Example 8 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 20 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0037] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0038] Example 9 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 30 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1.5 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0039] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0040] Example 10 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:1 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0041] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0042] Example 11 The preparation method of the biomimetic ceramic filter element is as follows: S31. Raw material preparation: Outer layer: 35g talc powder, 38g kaolin, 15g α-alumina, 14g ordinary starch with a particle size of 5-10μm and 5g polyvinyl alcohol, mixed evenly; Middle layer: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite with a particle size of 1-3μm and 5g polyvinyl alcohol, mixed evenly; Inner layer: 35g talc powder, 38g kaolin, 15g α-alumina, 11g starch nanocrystals with a particle size of 50-100nm, 4g polyvinyl alcohol and 2g polyethylene glycol 4000, mixed evenly; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: Heat to 600℃ at a heating rate of 5℃ / min and hold for 2 hours; heat to 1000℃ at a heating rate of 3℃ / min and hold for 1 hour; heat to 1350℃ at a heating rate of 3℃ / min and hold for 3 hours; cool to 800℃ at a cooling rate of 3℃ / min and hold for 1 hour, then allow to cool naturally to room temperature to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Cellulase, pectinase, and β-glucosidase were dissolved in 0.1 M citrate-phosphate buffer to obtain a concentration of 60 U / mL for cellulase, 40 U / mL for pectinase, and 25 U / mL for β-glucosidase. Glucosinolate was added, with a molar ratio of 1:2 for β-glucosidase. The mixture was pre-incubated at 46℃, pH 5.0, and 120 rpm for 40 min. 1% trehalose was added and mixed thoroughly to obtain the pre-incubation solution. Then, a solution of 1% agarose and 0.1% CaCl2 was added, with a volume ratio of 1:2 between the pre-incubation solution and the 1% agarose and 0.1% CaCl2 solution. The pH was adjusted to 5.5 to obtain the composite enzyme-buffered gel solution. S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of -0.09 MPa for 50 min to allow the composite enzyme-buffered gel solution to be drawn into the middle layer of the ceramic body. After removal, centrifuge at 400 rpm for 2 min and cool and set at 4℃ for 10 min to obtain the final product.

[0043] Measurements show that the outer pore size of the biomimetic ceramic filter element is 5-10 μm, the middle pore size is 1-3 μm, and the inner pore size is 50-100 nm.

[0044] Comparative Example 1 The preparation method of ordinary ceramic filter elements with non-gradient pore structure is as follows: S31. Raw material preparation: 35g talc powder, 38g kaolin, 15g α-alumina, 9g graphite (particle size 1-3μm), 5g polyvinyl alcohol, mix evenly without layering; S32. Molding and sintering: Dry pressing at 20MPa, sintering at 1350℃ for 3h (non-gradient sintering procedure). S33. Enzyme loading: Directly immerse in the complex enzyme solution (without gel immobilization) and dry at 60°C.

[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that the enzyme-substrate physical mixing loading was not pre-incubated, as detailed below: S31-S34 are the same as in Example 1; S35. Enzyme loading: The complex enzyme, glucosinolate (molar ratio 1:2), agarose and CaCl2 are physically mixed and then directly aspirated into the ceramic (no pre-incubation step).

[0046] Comparative Example 3 The difference between this comparative example and Example 1 is that the enzyme immobilization is without trehalose protection, as detailed below: S31-S34 are the same as in Example 1; S35. Enzyme solution: Trehalose is omitted, and the rest is the same as in Example 1 (compound enzyme + glucosinolate pre-incubation).

[0047] Comparative Example 4 The difference between this comparative example and Example 1 is that a single enzyme is used (without the synergistic effect of a complex enzyme), as detailed below: S31-S34 are the same as in Example 1; S35. Enzyme solution: Use only β-glucosidase (25 U / mL), without cellulase / pectinase.

[0048] Performance testing: Average aperture: Mercury intrusion porosimetry (MIP) (ASTM D4404): measures the pore distribution and takes the most probable pore size (peak pore size).

[0049] Enzyme loading: BCA protein quantification method: After pulverizing the ceramic filter element, the enzyme protein was extracted with 1% SDS solution and the absorbance at 562 nm was measured.

[0050] Enzyme activity recovery: pNPG method: Using p-nitrophenol-β-D-glucoside (pNPG) as substrate, the change in absorbance at 405 nm was measured, and the enzyme activity before and after immobilization was compared. The calculation formula is as follows:

[0051] Enzyme activity half-life: Accelerated aging experiment: Store at 55℃, take samples periodically to determine the remaining enzyme activity, and calculate the half-life by fitting a first-order kinetic curve.

[0052] The results are shown in Table 1 below: Table 1

[0053] As shown in Table 1 above, the single pore size (2.5 μm) of Comparative Example 1 resulted in low enzyme loading and poor activity recovery (65.3%). The enzyme loading of Examples 1-11 (7.95-8.50 mg / g) was significantly higher than that of Comparative Example 1. The polydopamine coating enhanced surface hydrophilicity and promoted uniform distribution of the enzyme gel. In Example 1, pre-incubation (enzyme-substrate molar ratio 1:2) combined with trehalose / agarose-Ca 2+ The gelation method achieved an activity recovery rate of 91.3%, while Comparative Example 2 (without pre-incubation) only achieved 68.0%, mainly due to the lack of pre-binding of enzyme and substrate, resulting in reduced catalytic efficiency. Comparative Example 3 (without trehalose) saw a decrease to 50.2%, indicating that pre-incubation stabilized the enzyme conformation and trehalose prevented thermal denaturation.

[0054] Example 12 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 15rpm, oil output speed 1.3L / min. The biomimetic ceramic filter element prepared in Example 3 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0055] Example 13 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 20rpm, oil output speed 1.5L / min. The biomimetic ceramic filter element prepared in Example 3 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0056] Comparative Example 5 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 10rpm, oil output speed 0.8L / min. The biomimetic ceramic filter element prepared in Example 3 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0057] Comparative Example 6 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 25rpm, oil output speed 1.7L / min. The biomimetic ceramic filter element prepared in Example 3 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0058] Comparative Example 7 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 20rpm, oil output speed 1.5L / min, and the biomimetic ceramic filter element prepared in Comparative Example 1 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0059] Comparative Example 8 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed was fed into a screw press. The screw press parameters were: 55℃, screw speed 20rpm, oil output speed 1.5L / min, and the biomimetic ceramic filter element prepared in Comparative Example 2 was installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0060] Comparative Example 9 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 20rpm, oil output speed 1.5L / min, and the biomimetic ceramic filter element prepared in Comparative Example 3 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0061] Comparative Example 10 The preparation method of rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 20%; S2. Enzymatic activation: Spray with a β-glucosidase solution at pH 5.5 at a rate of 40 U / g rapeseed, and let stand at 55℃ for 1.5 h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press. The screw press parameters are: 55℃, screw speed 20rpm, oil output speed 1.5L / min, and the biomimetic ceramic filter element prepared in Comparative Example 4 is installed at the oil outlet. S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; S5. Every 8 hours of operation, the biomimetic ceramic filter element is automatically backwashed with 0.1M NaOH solution to restore the flow rate.

[0062] Performance testing: The properties of the rapeseed oils prepared in each embodiment and comparative example were determined, including: (1) Residual oil rate: According to GB / T 15687-2008, the residue after pressing is extracted with petroleum ether using Soxhlet extraction, and the mass percentage of residual oil is calculated; (2) Acid value: determined according to standard GB 5009.229-2016; (3) Polyphenol content: determined by HPLC (GB / T 22244-2008); (4) Phospholipid residue: According to GB / T 5537-2008, molybdenum blue colorimetric method: the oil sample reacts with ammonium molybdate, and the absorbance at 715 nm is measured; (5) Enzyme activity retention rate: pNPG method: Reaction system: 1 mL 1 mM pNPG + 0.1 mL enzyme solution (40℃, pH 5.0). To terminate the reaction: use 1 mL of 1M Na2CO3 and measure the absorbance at 405 nm. Calculation formula: ; (6) Filter cartridge flux decay rate: The initial flux (Q0) and the flux after 8 hours (Q8) are measured, and the formula is as follows: ; The results are shown in Table 2 below: Table 2

[0063] As shown in Table 2 above, Example 13 had the lowest residual oil rate (9.8%), significantly better than the low-speed Comparative Example 5 (10 rpm / 0.8 L / min, residual oil rate 18.7%) and the high-speed Comparative Example 6 (25 rpm / 1.7 L / min, residual oil rate 12.3%). This indicates that moderately increasing the rotation speed (15 → ​​20 rpm) can enhance shear force and promote oil release, but excessively high rotation speed (25 rpm) leads to insufficient rapeseed retention time and incomplete pressing. Compared to Comparative Example 7 (non-gradient filter element), the residual oil rate increased to 15.2%, mainly because the single pore size (2.5 μm) is prone to clogging, which in turn increases the pressing resistance. Example 13 exhibited the highest polyphenol content (132.45 mg / 100g), primarily due to the gentle filtration of the gradient filter: the outer layer's large pore size reduced mechanical damage, while the inner layer's nanopores (82 nm) retained impurities but released polyphenols. Simultaneously, β-glucosidase released bound polyphenols (such as glucosinolate hydrolysates). In contrast, Comparative Example 10 (single enzyme) had a polyphenol content of only 88.79 mg / 100g, mainly due to the loss of the synergistic degradation effect of the complex enzymes (cellulase / pectinase) on the cell wall. Example 13 also showed the lowest acid value (0.25) and phospholipid residue (45 ppm), primarily because the enzyme activity in the middle layer of the gradient filter continuously degraded phospholipids, and low-temperature pressing inhibited lipoxygenase activity, reducing the formation of free fatty acids. Example 13 showed an enzyme activity retention rate of 89.7%, significantly higher than Comparative Example 8 (without pre-incubation, 71.2%), mainly because the enzyme in Comparative Example 8 was prone to leakage due to physical adsorption. The difference between Example 12 (8.2%) and Example 13 (12.7%) stemmed from the oil output rate (1.3 vs 1.5 L / min). The higher flow rate increased the impurity retention load, but both were better than Comparative Example 6 (28.3%). This was mainly because the high-speed pressing in Comparative Example 6 resulted in more colloidal impurities clogging the filter element.

[0064] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis, characterized in that, Includes the following steps: S1. Raw material pretreatment: Crush the rapeseed to a particle size of 0.5-1mm and adjust the moisture content to 18-22%; S2. Enzymatic activation: Spray with β-glucosidase solution and let stand at 50-55℃ for 1-1.5h to obtain pretreated rapeseed; S3. Low-temperature pressing: The pretreated rapeseed is fed into a screw press, and a biomimetic ceramic filter element is installed at the oil outlet; S4. The rapeseed oil flowing through the biomimetic ceramic filter can be directly bottled to obtain the product; The biomimetic ceramic filter element is sintered using gradient sintering technology to form a porous structure with a dense outer layer and a sparse inner layer. It mainly consists of three layers: outer layer: 5-10μm macropores, simulating the sieve structure of a cell wall; middle layer: 1-3μm channels, filled with a composite enzyme-buffered gel solution with a pH of 5.

5. Inner layer: 50-100nm micropores, adsorbing phospholipids.

2. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 1, characterized in that: In step 2, the pH of the β-glucosidase solution is 5.5, and the spraying volume is 40 U / g rapeseed.

3. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 1, characterized in that: The parameters of the screw press in step 3 are: 53-57℃, screw speed 15-20rpm, and oil output speed 1.3-1.5L / min.

4. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 1, characterized in that: The preparation method of the biomimetic ceramic filter element is as follows, in parts by weight: S31. Raw material preparation: Outer layer: 35 parts talc powder, 38 parts kaolin, 15 parts α-alumina, 12-15 parts ordinary starch and 5 parts polyvinyl alcohol; Intermediate layer: 35 parts talc, 38 parts kaolin, 15 parts α-alumina, 8-10 parts graphite and 5 parts polyvinyl alcohol; Inner layer: 35 parts talc, 38 parts kaolin, 15 parts α-alumina, 10-12 parts starch nanocrystals, 4 parts polyvinyl alcohol and 2 parts polyethylene glycol 4000; S32. Gradient filling and dry pressing: The mold is filled with a 5mm thick outer layer, a 3mm thick middle layer, and a 2mm thick inner layer in sequence, and held under 20MPa pressure for 5 minutes to form a green blank. S33. Segmented sintering: 600℃ / 2h→1000℃ / 1h→1350℃ / 3h→800℃ / 1h, to obtain a gradient porous ceramic body; S34. Surface modification: The gradient porous ceramic body was activated by immersing it in a 3 mol / L NaOH solution at 60℃ for 30 min, and then immersed in a dopamine-Tris buffer solution at pH 8.5 and 2 mg / mL for 24 h to obtain a ceramic body with a polydopamine coating. S35. Enzyme solution preparation: Dissolve the complex enzyme in 0.1 M citrate-phosphate buffer, add glucosinolate, pre-incubate at 45-48℃, pH 5.0, and 100-120 rpm for 40 min, add 1% trehalose, mix well to obtain the pre-incubation solution, then add a solution of 1% agarose and 0.1% CaCl2 to adjust the pH to 5.5 to obtain the complex enzyme-buffered gel solution; S36. Immerse the ceramic body with polydopamine coating in a composite enzyme-buffered gel solution and adsorb it under a negative pressure of (-0.08)-(-0.1) MPa for 40-60 min, so that the composite enzyme-buffered gel solution is absorbed into the middle layer of the ceramic body. After taking it out, centrifuge it at a low speed of 300-500 rpm for 2 min, and cool it at 4℃ for 10 min to fix it.

5. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 4, characterized in that: In S31, the particle size of ordinary starch is 5-10 μm, the particle size of graphite is 1-3 μm, and the particle size of starch nanocrystals is 50-100 nm.

6. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 4, characterized in that: In step S33, the temperature is increased to 600°C at a heating rate of 5°C / min; increased to 1000°C at a heating rate of 3°C / min; increased to 1350°C at a heating rate of 3°C / min; decreased to 800°C at a cooling rate of 3°C / min; and then naturally cooled to room temperature after reaching 800°C.

7. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 4, characterized in that: The S35 complex enzyme consists of cellulase, pectinase, and β-glucosidase. After dissolution, the cellulase concentration is 60 U / mL, the pectinase concentration is 40 U / mL, and the β-glucosidase concentration is (20-30) U / mL.

8. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 4, characterized in that: The molar ratio of β-glucosidase to glucosinolate in S35 is 1:

2.

9. The method for preparing rapeseed oil with high polyphenol retention rate based on biomimetic enzymatic hydrolysis according to claim 4, characterized in that: The volume ratio of the pre-incubation solution and the solution of 1% agarose and 0.1% CaCl2 in S35 is 1:(1-2).

10. Rapeseed oil with high polyphenol retention rate prepared by the preparation method according to any one of claims 1-9.